What determines the innovative success of subsidized collaborative R&D projects? - Project-level evidence from Germany - Jutta Günther; Michael Schwartz; Francois Peglow; Michael Fritsch (Verein für Socialpolitik, 2010)
Systemic innovation theory emphasizes that innovations are the result of an interdependent exchange process between different organizations. This is reflected in the current paradigm in European innovation policy, which aims at the support of collaborative R&D and innovation projects bringing together science and industry. Building on a large data set using project-level evidence on 406 subsidized R&D cooperation projects, the present paper provides detailed insights on the relationship between the innovative success of R&D cooperation projects and project characteristics. Patent applications and publications are used as measures for direct outcomes of R&D projects, while we also differentiate between academic-industry projects and pure inter-firm projects. Main results of negative binomial regressions are that R&D projects' innovative output is positively related to university involvement, to projects' funding and international commercialization range of R&D. Duration of R&D projects positively affects project outcomes in terms of publications but not in terms of patent applications. No significant effects are found for spatial proximity among cooperation partners, for the engagement of an applied research institute and for large-firm involvement. Results are discussed with respect to the design of R&D cooperation support schemes.
Keywords: O31; O32; O38; 330